Cyclic AMP phosphodiesterase in Thermomonospora curvata. - Gerber, L (1987)
Cyclic AMP phosphodiesterase (PDE; EC 3.1.4.17) in Thermomonospora curvata was purified and characterized. Fractionation of cell extracts by ion-exchange and size-exclusion chromatography revealed four PDE isozymes, which differed markedly in molecular weight, theophylline sensitivity, pH optima, and substrate affinity. Although the enzyme was labile after purification, total recovery of PDE activity was fivefold that of the crude extract. PDE biosynthesis appeared sensitive to the growth phase, growth rate, and carbon source. PDE levels in batch cultures peaked and declined rapidly during mid-exponential-phase growth. In continuous culture, maximal PDE and cellulase production occurred at dilution rates yielding mean cell generation times of about 5 and 17 h, respectively. The addition of glucose to cellulose-grown cells caused declines in both cyclic AMP and PDE levels, suggesting that the enzyme was subject to, rather than the agent of, catabolite repression.